La filosofia della come metafilosofia - Manca, Danilo (Itinerari, 2024)
The aim of this essay is to show how three possible meanings in which the philosophy of literature can be understood help to reflect on the nature, genesis, methods and purposes of philosophy. Firstly, I will consider the philosophy of literature as a line of inquiry that makes literature the object of investigation. Secondly, I will focus on the instrumental use of literature in philosophy when it is considered as a source of exemplary cases. Finally, I will delve into the so-called “philosophy in literature”, that is, the ability to pose philosophical and metaphilosophical questions in literary form.